2016
DOI: 10.1177/1753425916631404
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated LL-37 as a modulator of the immune response

Abstract: Carbamylation (or carbamoylation) of lysine residues and protein N-termini is a ubiquitous, non-enzymatic post-translational modification. Carbamylation at sites of inflammation is due to cyanate formation during the neutrophil oxidative burst and may target lysine residues within the antimicrobial peptide LL-37, which is secreted by activated neutrophils. The bactericidal and immunomodulatory properties of LL-37 depend on its structure and cationic nature, which are conferred by arginine and lysine residues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 50 publications
0
45
1
1
Order By: Relevance
“…It is reported that LL37 can become a substrate for post-translational modifications such as citrullination and carbamylation ( 20 , 21 ). Of note, carbamylated proteins can be the targets of autoantibodies in PsA ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that LL37 can become a substrate for post-translational modifications such as citrullination and carbamylation ( 20 , 21 ). Of note, carbamylated proteins can be the targets of autoantibodies in PsA ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, another posttranslational modification affecting the cationicy of LL-37 has also been reported. Carbamylation results in the non-enzymatic conversion of lysine residues to neutral homocitrulline (65,66) and thus reduces the net positive charge of LL-37. Similarly to citrullinated LL-37, carbamylated LL-37 also displays reduced direct antibacterial activity and reduced ability to modulate LPS-mediated cytokine release (65), confirming the importance of positive charge in the normal function of LL-37.…”
Section: Discussionmentioning
confidence: 99%
“…In a grand scheme, LL-37 controls the expression of both pro-and anti-inflammatory cytokines during infection. In the presence of physiological concentrations of cyanate, LL-37 undergoes compositional changes yielding a variety of carbamylated peptides [83]. As small structural changes as carbamylation have diverse effects on the biological properties of LL-37, most notably conversion from anti-inflammatory to pro-inflammatory properties.…”
Section: Human Cathelicidinsmentioning
confidence: 99%